RELATIONSHIP BETWEEN KNOWLEDGE OF LEARNING MANAGEMENT AND COMMITMENTS ON TASK TO THE TEACHER PERFORMANCE OF MADRASAH TSANAWIYAH STATE 3 MEDAN - Desi Yudiana (State Islamic University of North Sumatra Indonesia, 2019)
The purpose of this study is to determine the relationship: (1) knowledge management learning on the performance of teachers Madrasah Tsanawiyah Negeri 3 Medan; (2) commitment to tasks to the performance of Madrasah Tsanawiyah Negeri 3 Medan teachers; and (3) knowledge management knowledge and commitment on task simultaneously to performance of Madrasah Tsanawiyah Negeri 3 Medan teacher. The subjects of the study were MTs Negeri 3 Medan teachers with a total sample of 54 peoples. Descriptive research method that aims to obtain information about a symptom in the study. The results showed: (1) there is a significant correlation between the knowledge of learning management on teacher performance as ry1.2 = 0,442 > r-table = 0,266 with significance 0,001; (2) there is a significant relation between commitment on task to teacher performance equal to ry2.1 = 0,592 > r-table = 0,266 with significance 0,000; and (3) there is a significant correlation between learning management knowledge and commitment on task simultaneously to teacher performance equal to Ry(12) = 0,665 > r-table = 0,266 with significance 0,000. Knowledge of learning management and commitment to tasks together contributes 44.3% to teacher performance, and the rest is determined by other circumstances. The results of this study conclude that knowledge of learning management and commitment to the task has a relationship to the performance of teachers MTs Negeri 3 Medan. Thus, it can be said that improving the performance of MTs Negeri 3 Medan teachers can be done by improving the knowledge of learning management and commitment to good tasks. Keywords: Knowledge management learning, Commitment to the task, Teacher performance